Differential Contributions of MYCs to Insect Defense Reveals Flavonoids Alleviating Growth Inhibition Caused by Wounding in Arabidopsis - Wang, Dan-Dan; Li, Pai; Chen, Qiu-Yi; Chen, Xue-Ying; Yan, Zi-Wei; Wang, Mu-Yang; Mao, Ying-Bo (Frontiers in Plant Science, 2021)
In Arabidopsis, the basic Helix-Loop-Helix transcription factors (TFs) MYC2, MYC3 and MYC4 are involved in not only defense against insects but also many other biological processes. We found that despite the functional redundancy, MYCs-related mutants displayed different resistance to cotton bollworm (Helicoverpa armigera). To screen out the most likely genes involved in defense against insects, we analyzed the correlation of gene expression with the cotton bollworm resistance in wildtype and MYCs-related mutants. In total, the expressions of 94 genes in untreated plants and 545 genes in wounded plants were strongly correlated with insect resistance and these genes were defined as MGAIs (MYC-related genes against insect). MYC3 has the most impact on the total MGAIs expressions. GO analysis reveals that besides biosynthesis pathway of glucosinolates, the well-known defense compounds, the MGAIs are also enriched in flavonoids biosynthesis. Moreover, MYC3 dominantly functioned on the gene expressions of flavonoids biosynthesis. WGCNA revealed that AAE18 which is involved in activating auxin precursors 2,4-dichlorophenoxybutyric acid (2,4-DB) and another two auxin response genes were highly co-expressed with flavonoids biosynthesis genes. Under wounding treatment, the wildtype plants exhibit better growth performance than chs which is defected in flavonoids biosynthesis. Our data demonstrates the dominant contributions of MYC3 on cotton bollworm resistance and the possible role of flavonoids on plant defense by coordinating with auxin signaling to alleviate growth inhibition caused by wounding in Arabidopsis.